GAYA KOMUNIKASI USTADZ TONI YUFIDA DALAM MENYAMPAIKAN PESAN DAKWAH - Saputri, Nur Pita; Slamet, Moh (Universitas Hasyim Asy'ari, 2023)
The study aims to understand Ustadz Toni Yufida's communication style in delivering Islamic preaching messages during religious gatherings in the village of Delima Jaya, Kerinci Kanan District, Siak Regency, Riau Province. It investigates the impact of Ustadz Toni Yufida's preaching messages on the attendees of the religious gatherings in Delima Jaya Village. This writing is a descriptive and qualitative field study that gathers data through interview techniques, observation, and documentation. The results of this study indicate that Ustadz Toni Yufida's communication style is characterized by direct and assertive communication, without indications of passive, aggressive, or passive-aggressive communication. The impact of his preaching messages is seen in the community's ability to draw valuable lessons from them, which can be applied in their daily lives. These lessons encompass knowledge about beliefs (aqidah), monotheism (tauhid), and Islamic jurisprudence (fiqh), providing a deeper understanding of genuine life principles.